Genome-wide association study identifies loci and candidate genes for non-idiopathic pulmonary hypertension in Eastern Chinese Han population - Caiyong Yin; Kai Li; Yanfang Yu; Huijie Huang; Youjia Yu; Zhongqun Wang; Jinchuan Yan; Yan Pu; Zheng Li; Ding Li; Peng Chen; Feng Chen (BMC Pulmonary Medicine, 2018)
Abstract Background Pulmonary hypertension (PH) is a rare disease characterized by proliferation and occlusion of small pulmonary arterioles, which has been associated with a high mortality rate. The pathogenesis of PH is complex and incompletely understood, which includes both genetic and environmental factors that alter vascular structure and function. Methods Thus we aimed to reveal the potential genetic etiology of PH by targeting 143 tag SNPs of 14 candidate genes. Totally 208 individuals from Chinese Han population were enrolled in the present study, including 109 non-idiopathic PH patients and 99 healthy controls. Results The data revealed that 2 SNPs were associated with PH overall susceptibility at p < 3×10− 4 after Bonferroni correction. The top hit was rs6557421 (p = 4.5×10− 9), located within Nox3 gene on chromosome 6. Another SNP rs3744439 located in Tbx4 gene, also showed evidence of association with PH susceptibility (p = 1.2×10− 6). The distribution of genotype frequencies of rs6557421 and rs3744439 have dramatic differences between PH patients and controls. Individuals with rs6557421 TT genotype had a 10.72-fold/14.20-fold increased risk to develop PH when compared with GG or GG/GT carriers in codominant or recessive model, respectively (TT versus GG: 95%CI = 4.79–24.00; TT versus GG/GT: 95%CI = 6.65–30.33). As for rs3744439, AG genotype only occurred in healthy controls but has not been observed in PH patients. We further validated the result by using 26 different populations from five regions around the globe, including African (AFR), American (AMR), East Asian (EAS), European (EUR), and South Asian (SAS). In consistent with the present case-control study’s results, significantly different genotype frequencies of the observed SNPs existed between PH patients and healthy individuals from all over the world. Conclusions The results suggested that rs6557421 variant in Nox3 and rs3744439 variant in Tbx4 might have potential effect on individual susceptibility to pulmonary hypertension, which could lead to therapeutic or diagnosis approaches in PH.